Predictive value of negative cone margin status for risk of residual disease among women with cervical adenocarcinoma in situ - Chumnan Kietpeerakool (2018)
Objective: To determine the value of negative cone margins in predicting residual disease in women with adenocarcinoma in situ (ACIS). Methods: Data were retrospectively analyzed from 60 women with ACIS who underwent conization at Chiang Mai University Hospital between March, 1998, and December, 2010. Negative margin status was defined as absence of neoplastic epithelium at all margins, coupled with presence of normal cervical epithelium. The association between the incidence of residual lesions and cone margin status was analyzed via χ2or Fisher exact test. Results: When adjusted for age and completeness of visualization of the cervical squamocolumnar junction during colposcopy, women who underwent loop electrosurgical excision procedure were 4 times more likely to have positive cone margins than those who underwent cold-knife conization (95% CI, 1.13-16.43). Residual disease was not found among 26 women who had negative cone margins, but was observed in 17 (65.4%) of 26 women with positive cone margins (P < 0.001). Conclusion: Women with ACIS who had negative cone margins were found to have a notably low risk of residual disease. Adherence to the standard method of cone sampling and criteria for negative margin status might contribute to a high predictive value of negative cone margins. © 2012 International Federation of Gynecology and Obstetrics.